2018
DOI: 10.1002/aenm.201802365
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electron Density of Aromatic Solvent for Stable Solid‐Electrolyte‐Interphase Layer in Carbonate‐Based Lithium Metal Batteries

Abstract: green electric transportation due to its low redox potential (−3.04 V vs standard hydrogen electrode) and unprecedented theoretical capacity (3860 mAh g −1 or 2060 mAh mL −1 ). [1] In spite of these advantages, a substantial gap remains before practical application due to vulnerable dendritic growth during repeated Li deposition and stripping. Dendrite growth causes indiscriminate electrolyte decomposition and dead Li, resulting in inferior charge-discharge reversibility and ultimately severe capacity fading.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…Numerous approaches have been proposed to address issues associated with Li‐dendrite growth. A variety of electrolyte additives were introduced, including Cs + and Rb + , ionic liquids, co‐solvents, vinylene carbonate, LiNO 3 and polysulfides . These additives were used to promote stable SEI layers by enhancing the mechanical properties and the Li‐ion diffusivity or manipulating electrostatic fields near the Li electrode surface.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous approaches have been proposed to address issues associated with Li‐dendrite growth. A variety of electrolyte additives were introduced, including Cs + and Rb + , ionic liquids, co‐solvents, vinylene carbonate, LiNO 3 and polysulfides . These additives were used to promote stable SEI layers by enhancing the mechanical properties and the Li‐ion diffusivity or manipulating electrostatic fields near the Li electrode surface.…”
Section: Figurementioning
confidence: 99%
“…[2] Numerous approaches have been proposed to address issues associated with Li-dendrite growth. Av ariety of electrolyte additives were introduced, including Cs + and Rb + , [3] ionic liquids, [4] co-solvents, [5] vinylene carbonate, [6] LiNO 3 and polysulfides. [7] These additives were used to promote stable SEI layers by enhancing the mechanical properties and the Li-ion diffusivity or manipulating electrostatic fields near the Li electrode surface.T he addition of lithium fluoride (LiF) was found to be particularly beneficial [8] from the perspective of both, mechanical stability and ionic conductivity.I na na ttempt to enhance the mechanical stability of SEI layers and Li-host structures,m ore recently also elastic polymers were incorporated.…”
mentioning
confidence: 99%
“…The other approach is to stabilize the SEI. Strategies including the exploitation of electrolyte additives (24)(25)(26)(27)(28), artificial protection layers (29)(30)(31)(32), and solid-state electrolytes (4,(33)(34)(35)(36) have been developed to regulate and modify the physicochemical properties of the Li/electrolyte interface (37), leading to uniform Li + ion flux distribution and thus stable Li electroplating. At present, most reported protocols, however, only focused on either inducing uniform Li nucleation or stabilizing the SEI.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Yoo et al suggested aromatic compounds with different functional groups as electrolyte solvents for the formation of a stable SEI layer in carbonatebased Li metal batteries. [203] To form a uniform and rigid SEI layer on the Li metal, the study used the bonding characteristics of benzene rings that do leading to polymeric branch structures in polymerization after initiating itself due to being three double bonds resonance. In addition, three different aromatic compounds, benzene (Ben), toluene (Tol), and trifluorotoluene (Tof), were chosen for the study because the electron density determined by the functional group attached to the benzene group was found to influence the polymerization, as shown in Figure 11a.…”
Section: Artificial Layers Driven By Electrolyte Component Decompositionmentioning
confidence: 99%